Superiority of endoscopic transsphenoidal pituitary surgery to microscopic transseptal pituitary surgery for treatment of Cushing's disease - Zhang,Ting (2021)
SUMMARY OBJECTIVE: This study aims to compare the efficacy and safety of endoscopic transsphenoidal pituitary surgery and microscopic transseptal pituitary surgery in the treatment of Cushing's disease (CD). METHODS: A total of 46 patients with CD were randomized into endoscopic group and microscopic group, with 23 cases in each group. The endoscopic group received the endoscopic transsphenoidal pituitary surgery, and the microscopic group received the microscopic transseptal pituitary surgery. The retrospective data, surgical outcomes, surgical cure rates, and complications in two groups were compared. RESULTS: Compared with microscopic group, the operative time was significantly shorter (p<0.05), the estimated blood loss was significantly less (p<0.05), and the hospital stay was significantly shorter (p<0.05) in endoscopic group. The surgical cure rate in endoscopic and microscopic groups was 69.56% and 60.86%, respectively, with no significant difference between the two groups (p>0.05). The incidence of complications in endoscopic group was significantly lower than that in microscopic group (p<0.01). CONCLUSIONS: For the treatment of CD, the efficacy of endoscopic transsphenoidal pituitary surgery is basically the same as that of traditional microscopic transseptal pituitary surgery. However, the endoscopic surgery can further shorten the operative time, reduce the estimated blood loss, shorten the hospital stay, and reduce the complications.